Dinamika Historiografi Hadis di Kalangan Sunni - Nur Hidayah; Anisa Nilam Cahya (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This article explores the history of hadith writing among the Sunnis from its inception to its development. This research applied the qualitative method using the literature study technique. The desk study approach was used to collect the necessary data to identify relevant models and processes of hadith historiography among the Sunnis, as well as to provide information on the role of Sunni scholars of hadith in the digital era. The study found that Hadith historiography among the Sunnis is not only limited to the political issues between the Sunnis and the Shias. The article reveals most of the emergence of the sunni school as well as the historiography of hadith starting from the time of the Prophet, companions, tabi'in, mutaqadimin and muta'akhirin. Then, along with the books produced during the period of writing up to the present day. Meanwhile, the historical evolution of writing about hadith is more inclined towards topics that specifically aim to intertextualize it with various multidisciplinary sciences. In addition, to generate more knowledge, Sunni scholars have followed and provided insight into the Hadith to the wider community and Hadith academics using digital media in the form of applications that are easily accessible to the wider community and others.